LEGAL ANALYSIS ON THE SPECIAL MILITARY OPERATION OF RUSSIA IN UKRAINE BASED ON STATE SOVEREIGNTY PRINCIPLE - Muhammad Shidqi; Lena Farsia (Universitas Syiah Kuala, 2023)
This article analyses how is the Russia’s special military operation (SMO) in Ukraine according to the perspective of the State sovereignty principle, and how far the efforts of the United Nations (UN) in maintaining the world peace. This study utilized a normative research. The data in this research consists of primary and secondary data, obtained through international law resources (international covenant, convention and other international legal sources) and journals. The study reveal that Russian SMO in Ukraine has violated international law, particularly the state sovereignty principle which is a fundamental principle in international law. Furthermore, the United Nations as a peacekeeper organization has done any means in accordance to its obligation regulated in the UN Charter in maintaining peace. Russia must cease all military action and use a peaceful way, and the UN must call all of its member to be independent and provide a peaceful mediation to settle the conflicts.